Implementation of Interactive E-Books in Fostering Personal Safety in Early Childhood Education - Maulani, Aulia Syakinah; Kurnia Jayadinata, Asep; Ardiyanti, Dhea (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2026)
Objective: The purpose of this study is to determine the implementation and response to the use of interactive E-Books in early childhood self-safety learning. Personal safety education plays a crucial role in shaping children's attitudes and behaviors, enabling them to maintain their own safety and that of others. However, most PAUD institutions still do not have a structured concept of personal safety learning, so effective and interesting learning media for children are needed. Method: This study used a qualitative method with a case study approach. Data were collected through observations, interviews, and documentation involving early childhood educators and experts in learning activities using Interactive E-Books in Fostering Personal Safety in Early Childhood Education. Results: The results of the study show that this E-Book has a positive effect on increasing children's understanding of the concept of personal safety. Children show high enthusiasm, actively participate, and can understand safe actions in risky situations such as fires, earthquakes, or meeting strangers. Teachers consider that this media is interesting, communicative, and in accordance with the characteristics of children because it presents concrete, interactive, and fun learning. Novelty: This research strengthens the application of Bandura's Social Learning theory and Mayer's Multimedia Learning theory in the context of digital-based early childhood education. The integration of visual, audio, and character elements as behavioral models not only results in theoretical contributions regarding the effectiveness of interactive media but also makes practical contributions to the development of learning that is in accordance with the child's developmental needs. This innovation is in line with the Sustainable Development Goals (SDGs) points 3, 4, and 16, especially in supporting children's health and safety, providing quality education, and strengthening a safe and character-oriented learning environment.